2020
DOI: 10.1002/ajpa.24122
|View full text |Cite
|
Sign up to set email alerts
|

Form in the context of function: Fundamentals of an energy effective striding walk, the role of the plantigrade foot and its expected size

Abstract: What morphological and functional factors allow for the unique and characteristic upright striding walk of the hominin lineage? Predictive models of locomotion that arise from considering mechanisms of energy loss indicate that collision-like losses at the transition between stance limbs are important determinants of bipedal gait. Theoretical predictions argue that these collisional losses can be reduced by having "functional extra legs" which are physically the heel and the toe part of a single anatomical foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Even if the quantitative results above are viewed as—in detail—inaccurate, the scenario provides a principled, parsimonious account for a range of features of the human leg and foot. The knee should be approximately halfway down the leg; the heel should be shorter than the foot ahead of the ankle (in contrast to some current collisional models, which predict these to be symmetrical; [ 7 , 35 ]), and the toes should be relatively short and capable of some degree of dorsiflexion. While the functional implications of evolutionary reduction, and yet maintenance, of toe length has been considered [ 36 ], the scenario appears effective in accounting for a large range of qualitative features of human anatomy through simple energetic and geometric principles; and the quantitative predictions are also encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the quantitative results above are viewed as—in detail—inaccurate, the scenario provides a principled, parsimonious account for a range of features of the human leg and foot. The knee should be approximately halfway down the leg; the heel should be shorter than the foot ahead of the ankle (in contrast to some current collisional models, which predict these to be symmetrical; [ 7 , 35 ]), and the toes should be relatively short and capable of some degree of dorsiflexion. While the functional implications of evolutionary reduction, and yet maintenance, of toe length has been considered [ 36 ], the scenario appears effective in accounting for a large range of qualitative features of human anatomy through simple energetic and geometric principles; and the quantitative predictions are also encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…Grundy et al [5] found that the peak braking vertical GRF occurs when most of the foot is already in contact with the ground, but they were limited by the force plate technology of the time and did not examine in detail the consistency of this placement or whether it varies based on velocity, substrate or gradient. Croft & Bertram [6] recently examined the foot-ground interaction during bipedal walking through the lens of bipedal optimization, noting that the CoP, as it travels along the foot, plays royalsocietypublishing.org/journal/rsfs Interface Focus 11: 20200058 an integral role in predicting the overall dynamics of the system. The CoP at peak GRF indicates where the resultant of the contact forces between the foot and substrate act on the foot during a gait cycle.…”
Section: Ground Reaction Forcesmentioning
confidence: 99%
“…While the magnitude of these forces has received considerable attention (e.g. [3,4]), the location of the centre of pressure (CoP)—the resultant location of all forces applied to the sole—has been less investigated [5,6]. GRFs are a fundamental variable in most biomechanical analyses (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation